Answer:
[tex](-\frac{1}{3},2)[/tex]
Step-by-step explanation:
The x-coordinate of the vertex is [tex]x=-\frac{b}{2a}[/tex]
Therefore, [tex]x=-\frac{2}{2(3)}=-\frac{2}{6}=-\frac{1}{3}[/tex].
Now, the y-coordinate can be found by plugging in the x-coordinate into the function:
[tex]y=3x^2+2x+1[/tex]
[tex]y=3(-\frac{1}{3})^2+2(\frac{1}{3})+1[/tex]
[tex]y=3(\frac{1}{9})+\frac{2}{3}+1[/tex]
[tex]y=\frac{3}{9}+\frac{2}{3}+1[/tex]
[tex]y=\frac{1}{3}+\frac{2}{3}+1[/tex]
[tex]y=\frac{3}{3}+1[/tex]
[tex]y=1+1[/tex]
[tex]y=2[/tex]
So, the vertex of the graph is [tex](-\frac{1}{3},2)[/tex]